Revisión crítica de las concepciones habituales sobre el IVA - Vásquez del Rey Villaneva, Antonio (Revista de Derecho, 2019)
The legal approach to VAT has been traditionally weighed down by some economicconsiderations as well as by a too formalistic approach. From that perspective, VATshould not be regarded as a turnover tax, as it is usually seen in the EU environment.Moreover, for the purposes of a legal approach it is necessary to differentiate betweenthe goal of VAT, which is to levy a tax on consumption, and the mechanism by whichthat result is intended. In the first case, one must not oversize the existence of someexceptions to the ordinary functioning of VAT; otherwise, there is a risk of distortingthe truth as regards the justification of the tax on the ability to pay principle. Regardingspecifically the tax mechanism, the most widespread notion cannot be accepted eitheras its excessive formalism also leads to a somehow distorted view. The chargeable eventalways involves the payment of the tax, however, both the collection from customersand the right of deduction are key elements which do not allow categorizing VAT´slegal structure within the traditional tax law categories.
Keywords: VAT; GST; consumption tax; turnover tax; right of deduction; sales tax; tax neutrality